Global trends in tumor microenvironment-related research on tumor vaccine: a review and bibliometric analysis - Liu, Ying; Li, Sixin; Chen, Lu; Lin, Lin; Xu, Caijuan; Qiu, Huiwen; Li, Xinyu; Cao, Hui; Liu, Kun (Frontiers in Immunology, 2024)
Background: Tumor vaccines have become crucial in cancer immunotherapy, but, only a limited number of phase III clinical trials have demonstrated clinical efficacy. The crux of this issue is the inability of tumor vaccines to effectively harmonize the tumor microenvironment with its intricate interplay. One factor that can hinder the effectiveness of vaccines is the natural immunosuppressive element present in the tumor microenvironment. This element can lead to low rates of T-cell response specific to antigens and the development of acquired resistance. Conversely, anticancer vaccines alter the tumor microenvironment in conflicting manners, inducing both immune activation and immunological evasion. Hence, comprehending the correlation between tumor vaccines and the tumor microenvironment would establish a foundation for forthcoming tumor treatment.